Analisis Big Data dan Official Statistics dalam Melakukan Nowcasting Pertumbuhan Ekonomi Indonesia Sebelum dan Selama Pandemi COVID-19 - Muhammad Alfaris Kurniawan; Anna Triana Falentina (Seminar Nasional Official Statistics, 2022)
Economic growth data is very important and eagerly awaited by many people. However, the release of economic growth data has been delayed by up to five weeks so it is not able to provide actual data. Nowcasting method can be an alternative to support the actual data availability. Mixed Data Sampling (MIDAS) is one of the nowcasting methods that accommodates differences in the time-frame of the data. This study aims to form a nowcasting model of Indonesia's economic growth before and during the COVID-19 pandemic using official statistics and Big Data. The method used is MIDAS regression analysis which is applied to groups of variables and periods. Nowcasting results show that both official statistics and Big Data are able to predict economic growth well. For the pre-pandemic period, models that use Google Trends data have the best accuracy and models that use macroeconomics variables is the best estimator. Meanwhile, if the pandemic period is included, the model with combined variables is able to provide the best accuracy.